Investigação dos efeitos bioquímicos, proteômicos e estruturais da exposição prolongada ao cloreto de mercúrio sobre a medula espinhal de ratos - CORRÊA, Márcio Gonçalves (Universidade Federal do Pará, 2023)
Mercury chloride (HgCl2) is a pollutant widely found in the environment. This form of mercury is able to promote several damages to the Central Nervous System (CNS), including changes to the motor cortex, an area related to the planning and execution of motor activity. However, the effects of HgCl2 on the spinal cord, an important pathway for the communication between the CNS and the periphery, are still unknown. We exposed adult rats for 45 days to HgCl2, orally, to investigate the effects on oxidative biochemistry, proteomic profile, and spinal cord structures. Our results showed that exposure to this metal promoted increased levels of Hg in the medullary parenchyma, impaired oxidative biochemistry, changes in antioxidant system proteins, energy metabolism and myelin structure; as well as caused disruption in the myelin sheath and reduction in neuronal density. Thus, we conclude that prolonged exposure to HgCl2 triggers biochemical changes and in the expression of several proteins, resulting in damage to the myelin sheath and reduction of neurons in the spinal cord, which may be related to motor damage. Keywords: